Social Work in the hospital environment in times of pandemic of the COVID-19 (Research, Society and Development, 2020)
This article aims to analyze the role of the social worker in the hospital in the pandemic period of the COVID-19. The method used was the literature review. The literature search was carried out in the following databases: ScientificElectronic Library Online (SciELO) Web of Science and National Library of Medicine (PubMed / Medline), Virtual Health Library (VHL) and Google Scholar. For the choice of articles, the following health descriptors (decs.bvs.br) were considered combined with Boolean operators: COVID-19 AND Primary Health Care OR Health Education OR Prevention & Control OR Comprehensive Health Care. After the search, 27 articles were counted and 17 were excluded. The results found were that the hospital space is one of the priority areas for acting and becoming a professional social worker. Because it is the gateway to the health system and according to the SUS proposal, it is in accordance with the political ethics of social service and is based on the refraction of social issues, in this case refraction is the health process. The conclusions indicate that the work of the social worker is little recognized in hospitals, it is a job that requires responsibility and is irreplaceable, and it is the duty of the state to guarantee the minimum of rights and recognition to the profession.